2016
DOI: 10.1103/physreve.93.033123
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous capillary filling and wettability reversal in nanochannels

Abstract: This work revisits capillary filling dynamics in the regime of nanometric to subnanometric channels. Using molecular dynamics simulations of water in carbon nanotubes, we show that for tube radii below one nanometer, both the filling velocity and the Jurin rise vary nonmonotonically with the tube radius. Strikingly, with fixed chemical surface properties, this leads to confinement-induced reversal of the tube wettability from hydrophilic to hydrophobic for specific values of the radius. By comparing with a mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…Note that reversely the independent knowledge of the permeance in this system would allow to get much insights into the capillary pressure and disjoining effects at small scales. 47 This suggests further experimental work along these lines.…”
Section: Discussionmentioning
confidence: 90%
“…Note that reversely the independent knowledge of the permeance in this system would allow to get much insights into the capillary pressure and disjoining effects at small scales. 47 This suggests further experimental work along these lines.…”
Section: Discussionmentioning
confidence: 90%
“…Although the molecular origin of the solvation pressure is well-understood [38,42], reliable expressions for predicting its magnitude for various fluids are not available. However, Joly et al [41] have recently shown that an expression of the form…”
Section: Resultsmentioning
confidence: 99%
“…Thin-film dynamics can be analysed within the lubrification approximation 27 and in the limit of low Reynolds numbers. The fluctuation interface spectrum can be obtained from the Hamiltonian H h [ ] of the height fluctuations h. The energy functional depends on the Van der Waals interactions between the surfaces, possibly the discrete properties of the confined liquid 28,29 and also contributions associated with constraints fixing the average gap size. The dynamics for small height fluctuations are given by 27…”
Section: Transport and Dispersion Across Wiggling Nanopores Sophie Mamentioning
confidence: 99%